Extension of the Periods for Payment of Quota Increases Under the Fourteenth General Review of Quotas and the 2008 Reform. (Policy Papers; Policy Paper ;, 2016)
This paper proposes a further 34-day extension of the period for payment of quota increases under the Fourteenth General Review of Quotas ('Fourteenth Review'), and an extension for the payment of the quota increases under the 2008 Reform, through June 30, 2016. For the Fourteenth Review, under Board of Governors Resolution No. 66-2, each member shall pay to the Fund the increase in its quota within 30 days after the later of (a) the date on which it notifies the Fund of its consent, or (b) the date on which all of the general effectiveness conditions for the quota increases under the Fourteenth Review are met, provided that the Executive Board may extend the payment period as it may determine. The initial 30-day period for payments has been extended three times, most recently through May 27, 2016. Good progress is being made in implementing the quota payments. However, some members have indicated that they require additional time to complete internal procedures for the payment of quota increases. Staff is following up with the authorities in each of these cases to facilitate timely arrangements for payments.